2007
DOI: 10.1590/s0100-879x2007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid test for the evaluation of the activity of the prodrug hydroxymethylnitrofurazone in the processing of Trypanosoma cruzi messenger RNAs

Abstract: No fully effective treatment has been developed since the discovery of Chagas' disease by Carlos Chagas in 1909. Since drug-resistant Trypanosoma cruzi strains are occurring and the current therapy is effectiveness in the acute phase but with various adverse side effects, more studies are needed to characterize the susceptibility of T. cruzi to new drugs. Many natural and/or synthetic substances showing trypanocidal activity have been used, even though they are not likely to be turned into clinically approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…NFOH presented the same voltammetric behavior and electroactivity, indicating that the molecular modification performed in NF did not change its capacity to be reduced [15] . We and others have shown NFOH has 2-fold more cytotoxic activity than the parental compound NF against T. cruzi [15] , [16] . The mechanism of action of NFOH against T. cruzi is not completely clear; however, like all nitroheterocyclic compounds, it is enzymatically reduced at the nitro group resulting in the generation of nitroanion (RNO 2 •− ) and hydronitroxide (RNHO •− ) free radicals [17] .…”
Section: Introductionmentioning
confidence: 67%
“…NFOH presented the same voltammetric behavior and electroactivity, indicating that the molecular modification performed in NF did not change its capacity to be reduced [15] . We and others have shown NFOH has 2-fold more cytotoxic activity than the parental compound NF against T. cruzi [15] , [16] . The mechanism of action of NFOH against T. cruzi is not completely clear; however, like all nitroheterocyclic compounds, it is enzymatically reduced at the nitro group resulting in the generation of nitroanion (RNO 2 •− ) and hydronitroxide (RNHO •− ) free radicals [17] .…”
Section: Introductionmentioning
confidence: 67%
“…The literature showed that the inhibition of the trypanothione reductase was a possible mechanism of action of nitrofurazone (22,23,24); Trossini and coworkers (16) showed cruzipain inhibition and an increase of 30% in affinity for the enzyme. In addition, the most interesting and important point is the simplicity of the NFOH synthesis and its high yield (10), suggesting a very cheap compound for chemical scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…The native conformation of dUTpase from T. cruzi was determined and it revealed stumpy structural similarities with human dUTpase. This suggests certain specificity, making this enzyme another potential therapeutic target until today; however, no drug had demonstrated potential inhibition [145].…”
Section: Other Promising Targetsmentioning
confidence: 99%